Analisis Pengaruh Faktor-Faktor Dan Nilai Tukar Petani Kopi Masa Pandemi Covid-19 (Studi Kasus Kecamatan Atu Lintang Kabupaten Aceh Tengah - Suherman Suherman; Elly Susanti; Mujiburrahmad Mujiburrahmad (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
Coffee is a product that has good market opportunities both domestically and abroad. Most of Central Aceh's coffee production is a plantation commodity which is exported to the world market. Coffee commodity is the main source of livelihood for farmers, this is the prima donna plant of the farming community of Central Aceh Regency. Likewise, the people who live in Atu Lintang District, generally farmers in this area are coffee farmers. The impact of Covid-19 in Central Aceh entering the final month of the harvest period, the price of Gayo coffee is getting worse and sadder. The price of Gayo coffee at the farmer level has actually fallen to its lowest point due to the Covid-19 pandemic. Londong coffee (chary) is priced at Rp. 4,615/kg, from the price of Rp. 9.230/kg before the Covid-19 pandemic. Meanwhile, the cost of harvesting reaches IDR 25,000 per 13.3 kg. The price of green beans is currently below Rp. 65,000/kg, previously it was always above Rp. 65,000/kg for random types of coffee. This study aims to look at 1) the coffee farmers' exchange rate (NTP) during the Covid-19 pandemic, 2) what factors affect the coffee farmers' exchange rate (NTP). This research was conducted in Atu Lintang District, Central Aceh Regency. The analytical method used in this research is descriptive analysis, namely the analysis of quantitative data, both primary and secondary data. The results of the analysis are in the form of descriptions that are able to provide problem solving and achieve the objectives of research activities. The number of organic coffee farmers in Atu Lintang sub-district is 626 people. So that the number of respondents' samples was taken using the Slovin formula with a standard error of 10%. The analysis used is the exchange rate analysis of coffee farmers and multiple linear analysis (OLS). Based on the results of the study, the average exchange rate of coffee farmers during the Covid-19 pandemic, Atu Lintang District, Central Aceh Regency was 107%. Factors that affect the exchange rate of coffee farmers simultaneously or partially are land area, labor, production costs and production have a significant effect on the exchange rate of coffee farmers.